Attitudes, Perceptions, and Barriers in Learning Arabic Pharmaceutical Terminology among Female Pharmacy Students at Universitas Darussalam Gontor: English - Siti Nikmatul Rochma; Muthmainnah Choliq; Halimah As Sa’diah (Universitas Djuanda, 2025)
Abstract: This study examines the importance of investigating the attitudes, perceptions, and barriers faced by female pharmacy students at Darussalam Gontor University in learning and using Arabic pharmaceutical terminology. A descriptive quantitative research method was employed, utilizing a questionnaire distributed to 32 students. Data analysis was conducted using descriptive statistics such as mean, median, mode, standard deviation. The results indicated that the students generally had positive attitudes toward learning and using Arabic pharmaceutical terminology, recognizing its contribution to enhancing understanding of academic texts and improving professional competitiveness in the field of pharmacy. However, some barriers were identified, such as difficulties in memorizing and translating terminology between languages. The study recommends providing additional support in the area of learning Arabic terminology in pharmacy.